2015
DOI: 10.1037/a0037928
|View full text |Cite
|
Sign up to set email alerts
|

Cultural socialization and school readiness of African American and Latino preschoolers.

Abstract: Cultural socialization practices are common among ethnic minority parents and important for ethnic minority child development. However, little research has examined these practices among parents of very young children. In this study, we report on cultural socialization practices among a sample of parents of low income, African American (n = 179) and Latino (n = 220) preschool-age children in relation to children’s school readiness. Cultural socialization was assessed when children were 2½ years old, and child … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 57 publications
(92 reference statements)
4
48
1
Order By: Relevance
“…Developmental theories suggest that family is an important context for socializing youth (e.g., Bronfenbrenner, ), and that cultural socialization, in particular, is a normative process among ethnic‐racial minority families with young children (Hughes et al, ). Furthermore, in the small body of literature that has examined this aspect of socialization among families with Latino children, cultural socialization from caregivers has been positively associated with children's adjustment (Caughy & Owen, ; Quintana & Vera, ). Despite the potential benefits to adjustment of cultural socialization behaviors, measurement development in this area has been limited primarily to parents of adolescents and failed to distinguish between cultural socialization attitudes and behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Developmental theories suggest that family is an important context for socializing youth (e.g., Bronfenbrenner, ), and that cultural socialization, in particular, is a normative process among ethnic‐racial minority families with young children (Hughes et al, ). Furthermore, in the small body of literature that has examined this aspect of socialization among families with Latino children, cultural socialization from caregivers has been positively associated with children's adjustment (Caughy & Owen, ; Quintana & Vera, ). Despite the potential benefits to adjustment of cultural socialization behaviors, measurement development in this area has been limited primarily to parents of adolescents and failed to distinguish between cultural socialization attitudes and behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these limitations, the present study contributes to the field by providing two measures that can be used in research and practice to assess the cultural socialization attitudes and behaviors of mothers with preschool‐ and kindergarten‐aged children. For example, in clinical settings, the CSBM and CSAM could be administered as part of an initial assessment to better understand mothers' attitudes and behaviors concerning socializing their children about their ethnic‐racial culture, a process that has been linked with children's positive outcomes (e.g., Caughy & Owen, ). Further, both measurement tools could be useful as pre‐ and posttests for family‐focused intervention programs with mothers and their children that are designed to bolster children's positive youth development via family engagement in cultural socialization, which has been demonstrated to promote youth adjustment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A confirmatory factor analysis of the ratings of the larger study’s entire Hispanic sample of mothers indicated that a single factor for five of the maternal behaviors—sensitivity, cognitive stimulation, positive regard, negative regard, and detachment—fit the data best (Caughy & Owen, 2014), χ 2 (2) = 4.11, p = .13, comparative fit index = 1.00, Tucker–Lewis index = .99, root mean square error of approximation = .07, sample size 220. A maternal sensitivity composite was formed as the sum of the global 5-point ratings of sensitivity/responsiveness to child, cognitive stimulation, detachment (reversed), positive regard for child, and negative regard for child (reversed).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to these enculturation practices, Latino parents also socialize their children in ways that help them to be more successful. One study found that even in early childhood, Latino and African American children's identification with their culture was associated with positive outcomes including better academic skills, behavior, and receptive language (Caughy & Owen, 2015). Another study with high school students found that Latinos who received socialization messages from family were more likely to have started high school with a clear sense of their own racial-ethnic identity, which continued to develop in a positive direction as they became more engaged throughout high school (Douglass & Umaña-Taylor, 2015).…”
Section: African American Valuesmentioning
confidence: 99%